2007
DOI: 10.1007/s10681-007-9628-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the compactum locus in wheat (Triticum aestivum L.) and its relationship to other spike morphology genes of the Triticeae

Abstract: The spikes of club wheat are signiWcantly more compact than spikes of common wheat due to the action of the dominant allele of the compactum (C) locus. Little is known about the location of C on chromosome 2D and the relationship between C and to other spike-compacting genes. Thus, a study was undertaken to place C on linkage maps and a chromosome deletion bin, and to assess its relatedness to the spike compacting genes zeocriton (Zeo) from barley and soft glume (Sog) from T. monococcum. Genetic mapping was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 32 publications
4
94
3
3
Order By: Relevance
“…Homologs of HvAP2 are known in rice and maize, and recently a putative ortholog in wheat, TaAP2 (Fig S2), has been shown to be cleaved by miR172 (27). A dominant compact spike locus, COMPACTUM, is located on wheat chromosome 2D, but previous studies have indicated that this locus is not orthologous to ZEO (26). In agreement, we failed to identify mutations in the miR172-binding site from a range of COMPACTUM wheat cultivars.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Homologs of HvAP2 are known in rice and maize, and recently a putative ortholog in wheat, TaAP2 (Fig S2), has been shown to be cleaved by miR172 (27). A dominant compact spike locus, COMPACTUM, is located on wheat chromosome 2D, but previous studies have indicated that this locus is not orthologous to ZEO (26). In agreement, we failed to identify mutations in the miR172-binding site from a range of COMPACTUM wheat cultivars.…”
Section: Discussionsupporting
confidence: 81%
“…S2). In wheat, two loci associated with spike density, COMPACTUM (C) and SOFT OUTER GLUME (SOG), map to the group 2 chromosomes (26). We explored whether mutations in the miR172-binding site of TaAP2 were responsible for the COMPACTUM phenotype.…”
Section: Reduced Mirna-guided Cleavage Results In Heterochrony and Shmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main genes/loci are involved in spike shape control in wheat species: Q, C, C2 (Unrau, 1950;Rao, 1972;Goncharov and Gaidalenok, 2005;Simons et al, 2006;Johnson et al, 2008;Zhang et al, 2011;Sormacheva et al, 2015) ( Table 1). The alleles of 5AQ gene, which determines the normal and spelt spike shape in different wheat species, are described above.…”
Section: Dobrovolskaya Et Al 2015mentioning
confidence: 99%
“…Mutation giving rise to the dominant allele C resulted in the origin of club wheat, thus the investigation of this gene is important for the taxonomy of wheat species (Johnson et al, 2008). C2 gene controlling the compact spike characteristic in T. sphaerococcum is not allelic to gene C of T. compactum (Goncharov and Gaidalenok, 2005).…”
Section: Dobrovolskaya Et Al 2015mentioning
confidence: 99%